Implementasi Algoritma Fisher Yates Pada Media Pembelajaran Aksara Lontara Berbasis Augmented reality - Mirfan; Muhammad Yaumi; Erwin Akib (Prosiding SISFOTEK, 2024)
The teaching and learning process carried out using the lecture method without the support of learning media, will result in students getting bored so that students do not have the enthusiasm to learn. Meanwhile, the impact when the questions are not randomized in the learning media causes monotonous learning so that students will face the same sequence of questions every time. they learn, causing boredom and reducing interest and involvement in the learning process. Increased Memorization Without Understanding: Users may only memorize the sequence and answers to questions without truly understanding the material, reducing the effectiveness of learning and in-depth understanding of concepts. This research aims to Design Literacy Learning Media Lontara Based on Augmented Reality and Implementing the Fisher-Yates Algorithm Lontara Script Learning Media Based on Android Augmented Reality. The research design used is Unified Modeling Language (UML) which is designed in a structured manner consisting of use case diagram model designs, activity diagrams, sequence diagrams and class diagrams, software applications using Unity, Vuforia using the Fisher-Yates Algorithm. Results of the research This is the Fisher-Yates algorithm ensuring the order of the questions is always random every time it is run. This makes the user's learning experience more dynamic and interesting. This algorithm is very effective in creating variations in the presentation of questions